2015
DOI: 10.1007/s10488-014-0612-y
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of Shared Decision Making with Parental Perceptions of Child Mental Health Functioning and Care

Abstract: Experts encourage parents and practitioners to engage in shared decision making (SDM) to provide high quality child mental health care. However, little is known regarding SDM among families of children with common mental health conditions. The objectives of this study were to examine associations between parental report of SDM and parental perceptions of (a) receiving child mental health care and (b) child mental health functioning. We analyzed cross-sectional data on children with a common mental health condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 21 publications
1
13
1
2
Order By: Relevance
“…Covariates. Consistent with previous research using data from the NSCH, we included the following control variables: gender, income based on federal poverty level, highest level of education, and primary language spoken in the home (e.g., Butler et al, 2015;Weller et al, 2018;Weller et al, 2019).…”
Section: Indicators Of Social Determinants Of Healthmentioning
confidence: 99%
“…Covariates. Consistent with previous research using data from the NSCH, we included the following control variables: gender, income based on federal poverty level, highest level of education, and primary language spoken in the home (e.g., Butler et al, 2015;Weller et al, 2018;Weller et al, 2019).…”
Section: Indicators Of Social Determinants Of Healthmentioning
confidence: 99%
“…Research to date has outlined that most SDM interventions focus on externalising difficulties (Cheng et al, ). Despite this, recent research suggests that the prevalence of internalising difficulties is increasing in young people (Deighton et al, ; Fink et al, ) and that increased severity of difficulty, rather than whether difficulties are classified as internalising or externalising, predicts lower levels of SDM (Butler, Weller, & Titus, ). When interventions do exist for internalising difficulties, they appear to be targeted at ‘older’ teenagers (Simmons, Elmes, Mckenzie, Trevena, & Hetrick, ; Simmons et al, ) who may be attending the appointment without parents and are ‘competent to consent’ to treatment decisions.…”
Section: Introductionmentioning
confidence: 99%
“…The scoping review also identified that most approaches to SDM tend to focus on externalising difficulties [6]. However, research suggests that increasing severity of both internalising and externalising difficulties of young people has been found to predict SDM [8, 1113]. There is increasing evidence of rising rates of internalising difficulties in youth, particularly in girls, with reporting raised anxiety and depression [14, 15].…”
Section: Introductionmentioning
confidence: 99%